Monte Carlo simulation to optimize polymyxin B dosing regimens for the treatment of Gram-negative bacteremia - Yu, Yingying; He, Zheng; Wang, Chengcheng (Frontiers in Cellular and Infection Microbiology, 2025)
ObjectiveThis study aimed to predict and evaluate the efficacy of various polymyxin B dosing regimens for Gram-negative bacteremia using Monte Carlo simulation, with a specific focus on assessing the efficacy in patients receiving continuous renal replacement therapy (CRRT). The goal was to optimize clinical dosing regimens and guide rational polymyxin B use in practice.MethodsA total of 1,939 Gram-negative bacterial strains were analyzed, collected between April 2019 and December 2021 through the China Bloodstream Gram-negative Pathogens Antimicrobial Resistance and Virulence Surveillance Network (CARVIS-NET). Pharmacokinetic parameters of polymyxin B from existing literature were used to conduct a Monte Carlo simulation based on pharmacokinetic/pharmacodynamic (PK/PD) theory. The probability of target attainment (PTA) and cumulative fraction of response (CFR) were evaluated across various dosing regimens.ResultsThe main pathogens of Gram-negative bacteremia were Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa, and Acinetobacter baumannii, all of which demonstrated high susceptibility to polymyxin B. For pathogens with a minimum inhibitory concentration (MIC) ≤1 mg/L, all regimens achieved PTA >90%. However, when the MIC increased to 2 mg/L, the PTA for the 500,000 IU q12h regimen decreased to 77.53%, and at an MIC of 4 mg/L, none of the dosing regimens achieved a PTA >90%. For P. aeruginosa and K. pneumoniae with MIC ≤0.5 mg/L, all regimens demonstrated effectiveness. However, at MIC ≥1 mg/L, significant declines in PTA were observed, with the 500,000 IU q12h and 1.25 mg/kg q12h regimens yielding suboptimal outcomes. In CRRT patients, PTA values declined further, particularly against K. pneumoniae, raising concerns about potential treatment failure.ConclusionPolymyxin B demonstrates high efficacy for Gram-negative bacteremia with MIC ≤1 mg/L. However, efficacy diminishes as MIC increases, particularly for P. aeruginosa and K. pneumoniae, where 500,000 IU q12h and 1.25 mg/kg q12h regimens may result in suboptimal outcomes. For CRRT patients with K. pneumoniae bacteremia, therapeutic drug monitoring and dose adjustments are crucial to mitigate treatment failure risks.